Modeling Jupiter's cloud bands and decks 2. Distribution and motion of condensates - Zuchowski, L; Yamazaki, Y; Read, P (Elsevier, 2009)
A simple jovian cloud scheme has been developed for the Oxford Planetary Unified model System (OPUS). NH₃-ice, NH₄SH-solid, H₂O-liquid clouds have been modeled in Southern hemisphere limited area simulations of Jupiter. We found that either three or four of the condensates existed in the model. For a deep atmospheric water abundance close to solar composition, and NH₃-ice deck above 0.7 bar, and NH₄SH-solid deck above 2.5 bar and a H₂0-liquid deck with a base at about 7.5 bar and frozen cloud tops formed. If a depleted deep water abundance is assumed, however, a very compact cloud structure develops, where an H₂0-ice cloud forms by direct sublimation above 3 bar. The condensates constitute good tracers of atmospheric motion, and we have confirmed that zonal velocities determined from manual feature tracking in the modeled cloud layers agree reasonably well with the modeled zonal velocities. Dense and elevated clouds form over latitudes with strong atmospheric upwelling and depleted clouds exist over areas with strong downwelling. In the NH₃-ice deck this leads to elevated cloud bands over the zones in the domain and thin clouds over the belts, which is consistent with the observationally deduced distribution. Due to changes in the vertical velocity pattern in the deeper atmosphere, the NH₄SH-solid and water cloud decks are more uniform. This modeled cloud structure thus includes the possibility of more frequent water cloud observations in belts, as this deeper deck could be more easily detected under areas with thin NH₃-ice clouds. Large scale vortices appeared spontaneously in the model and were characterized by elevated NH₃-ice clouds, as expected from observations. These eddies leave the most discernible imprint on the lighter condensate particles of the uppermost layer.